Analisis Kesalahan An Nuthqu Huruf Al Arabiyyah di Taman Pendidikan Qur`an Al Wakil Pacitan: Kajian Fonologi - Aziz, Musani Abdul; Ahmadi, Ahmadi (YASIN, 2025)
The phenomenon of errors in the pronunciation of Arabic letters (an-nuthqu al-huruf al-‘Arabiyyah) has a significant impact on the quality of worship, particularly in reciting the Qur’an, which was revealed in eloquent Arabic. However, studies on this aspect remain limited. This study aims to analyze the factors influencing these errors and the forms they take in order to formulate concrete efforts to improve fluency in accordance with Arabic phonological rules. A descriptive qualitative approach was used with a random sampling technique, involving 20 ta’lim participants aged 50–75 years at TPQ Al Wakil Pacitan. Data collection techniques included interviews, observation, and documentation, which were then analyzed using thematic analysis. The findings reveal that low intensity of religious education, limited teacher competence, lack of interest in reading Arabic script, environmental and native language influence, and the perception that Arabic pronunciation is difficult are key factors contributing to pronunciation errors. The types of errors identified include the confusion of letters with similar makhraj and characteristics, the appearance of two sounds within a single phoneme, incomplete vowel articulation, and shifts between adjacent vowels. The conclusion of this study underscores the urgency of comprehensive religious education, particularly in Arabic phonology, so that Arabic letters can be pronounced correctly according to established rules. The practical implications highlight the importance of expanding the role of TPQ, not only for children but also as a platform for religious development among adults and the elderly.